Pouvez vous m'aider svp!! Je galère vraiment et mes parents ne veulent pas m'aider :((

Calcule les expressions suivantes:

R = ( - 3 + 9) + ( 4 - 11 ) - ( - 5 - 6 )
S = - 3 + 12 - ( 13 - 8 ) - ( 3 + 8 )
T = - 3 - [ 4 - ( 3 - 9 ) ]

1

Réponses

2014-05-12T18:42:37+02:00
R=(-3+9) + (4-11) - (-5-6)
R=6 + (-7) - (-11)
R=6 + (-7) + (+11)
R=6 + 11 + (-7)
R=17 + (-7)
R=10

S= -3 + 12 - (13-8) - (3+8)
S= -3 + 12 - (+5) - (+11)
S= -3 + 28
S= 25

T= -3 - [4 - (3-9)]
T= -3 - [4 - (-6)]
T= -3 - (-2)
T= -3 + (+2)
T= -1